Memahami Memahami Hubungan Antara Literasi Finansial Dan Pola Asuh Dengan Sosialisasi Finansial Orangtua Kepada Anak Usia Dini: 1. Pendahuluan, 2. Metode, 3. Hasil dan Pembahasan, 4. Kesimpulan, 5. Daftar Pustaka - Dewi Nurarifah; Yufiarti; Nurbiana Dhieni (Jurnal Pendidikan Anak Usia Dini Undiksha, 2023)
Someone with good financial literacy can manage personal finances, which will eventually get prosperity. This research seeks to understand the relationship pattern of parents' financial socialization behavior in early childhood education. For this reason, two main variables are used: the parents' current financial literacy and parenting style. Respondents are parents who have children aged 6 to 8 years. Three hundred eighty-six samples were taken using online and offline survey methods through a self-administered questionnaire. Data collection in the study was carried out using a non-test method in the form of parental financial literacy questionnaire sheets, parenting styles, and parental financial socialization. Data analysis was performed using univariate analysis to get an overview of the respondent's profile. A simple regression analysis was followed by analyzing the relationship between financial literacy and parenting variables separately with financial socialization. Then the final stage is to test the third hypothesis using multiple regression analysis. The results of the data analysis show that the standard beta coefficient value is 0.508 for the financial literacy variable and 0.283 for the parenting style variable. The results of this analysis indicate a significant relationship between financial literacy and parenting style with the financial socialization parents provide to early childhood.